Implementation of Community Health Center Accreditation Policy in Improving Service Quality at Campaka Community Health Center, Cianjur Regency - Zein, Edo Muhammad; Rohayati, Yeti; Kamil, Indriyati; Indah, Diani (Civiliza Publishing, Indonesia., 2025)
Community health centers (Puskesmas) play a leading role in Indonesia's healthcare system, making service quality a crucial public concern. This study aims to analyze the implementation of the Puskesmas accreditation policy and its impact on service quality at Campaka Community Health Center, Cianjur Regency. A qualitative case study approach was used, with data collected through in-depth interviews, participant observation, and document analysis. Data were analyzed using the Miles and Huberman interactive model. The results showed that accreditation implementation was effective during the preparation and survey phases, characterized by improved administrative governance, standardized procedures, improved facilities, and increased staff motivation. However, post-survey implementation showed a decline in consistency due to weak monitoring mechanisms, limited human resources, high administrative workloads, and decreased staff commitment. Accreditation had a positive effect on service quality across all SERVQUAL dimensions: reliability, responsiveness, tangibles, assurance, and empathy, but this improvement tended to be temporary and unsustainable. This study concluded that accreditation at Campaka Community Health Center is still event-oriented and has not been fully internalized as a quality culture. This study contributes to the policy implementation and health care literature by highlighting the importance of post-accreditation monitoring, human resource strengthening, and continuous quality management to ensure continuous improvement in primary health care.